Promotional Effectiveness of Indonesia's Ministry of Finance Library - Afidhan, Saiful (UI Scholars Hub, 2019)
This research discusses Indonesia’s Ministry of Finance Library’s promotional effectiveness in making users intrigued to utilize the library. This study aims to discover the library’s promotional effectiveness level based on overall promotional mix concepts consisted of six sub-variables. Those six sub-variables include personal selling, advertising, sales promotion, public relation and publicity, learning materials, and corporate design sub-variables. It is quantitative research by using a survey method. The survey was conducted on 100 respondents with a convenience sampling technique. Research results showed that promotional efforts done by the library were considered effective with a score of 79.28%. The highest score lied on personal selling sub-variable with a gain of 87.47%, and the lowest score was placed on public relation and publicity subvariable in the amount of 74.86%. This study suggests the library to improve the effectiveness of public relation and publicity sub-variable by maximizing social media use potentials as the promotional media. The research is expected to enrich literature regarding the strategy of promotional effectiveness measurement in libraries with more comprehensive promotional mix aspects.